Management approaches on maize (Zea Mays L.) Growth and yield using mesotrion and atrazine herbicides - Hussain, Iqtidar; Nazir, Muhammad Jawad; Gul, Hadia; Batool, Asma (Canadian Journal of Agriculture and Crops, 2025)
Maize (Zea mays L.) is a vital staple crop worldwide, but its productivity is often constrained by weed competition, particularly during early growth stages. This study evaluated the effectiveness of different weed management strategies using Mesotrione and Atrazine herbicides in combination with manual weeding across three maize varieties (MMRI Yellow, Pearl White, and Afghoiy). The experiment was conducted in summer 2019 under a Randomized Complete Block Design with three replications and five weed control treatments. Parameters recorded included weed density, biomass, plant height, ear height, stem diameter, leaf area, biological yield, and grain yield. Results indicated that both herbicide application and hand weeding significantly reduced weed density and biomass compared to untreated plots. The highest biological yield (18.28 t ha⁻¹) and grain yield (4.03 t ha⁻¹) were achieved with the recommended dose of Xiaowang (1X), which performed similarly to hand weeding. Moreover, a half dose of Xiaowang (½X) proved cost-effective while still delivering substantial weed suppression and yield improvements. These findings highlight the potential of integrated weed management strategies, where reduced herbicide doses combined with manual weeding can improve maize productivity while minimizing environmental and economic costs. The study suggests that herbicides, particularly at lower doses, can serve as an efficient and sustainable alternative to labor-intensive manual weeding in large-scale maize production systems.